Newer Hemostatic Agents - Franchini, Massimo; Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2015)
The mainstay of treatment of inherited coagulation disorders is based on the infusion of the deficient clotting factor, when available. Significant advances have been made over the past two decades in the production and availability of factor replacement products. In spite of such progression, several issue are still unsolved, the most important being the need for frequent factor concentrate infusions and the development of inhibitory alloantibodies. To overcome these important limitations, several newer hemostatic agents with an extended half-life are at an advanced stage of clinical development. After a brief overview of hemostasis, this narrative review summarizes the current knowledge on the most promising novel products for hemostasis. The current status of gene therapy for hemophilia, the only therapeutic option to definitively cure this inherited bleeding disorder, is also concisely discussed.
Keywords: clotting factor concentrates; new hemostatic products; extended half-life; hemophilia; inhibitors